PENINGKATAN EKONOMI KELOMPOK TANI-TERNAK GALAGATRA MELALUI PENGELOLAAN KEUANGAN, INOVASI PAKAN TERNAK LIMBAH PERTANIAN, DAN STRATEGI PEMASARAN - Amirullah, Sufyan; Edy, Sri Amalia; Mahanani, Agni Ayudha (Universitas Mataram, 2024)
Majene Regency is known for its horticultural production potential. Based on the West Sulawesi Central Statistics Agency (BPS), one of them is banana production which is ranked second in West Sulawesi Province. Majene Regency also has potential in the livestock sector, one of which is free-range chicken farming. Based on the Majene Regency Central Statistics Agency, during the last three years from 2021 to 2023, free-range chicken farming in Majene Regency has continued to increase. Based on the observation results of the proposing team, financial management carried out by the partner group is still very poor. The results of further observations found a lack of innovation and creativity from the Galagatra Livestock Farming Group causing the potential of existing resources not to be utilized optimally. One of the neglected horticultural potentials is banana stem waste which is only used by the Galagatra Group as ruminant animal feed. Banana stem waste should be able to be processed into several products that can provide benefits to the Galagatra Livestock Farmers Group, one of which is reducing animal feed production costs and agricultural production costs. It is known that banana stems can be processed into animal feed and fertilizer which has its own selling value and appeal. The objectives of this community partnership program (PKM) activity are 1) Increase partner members' financial management knowledge. 2) Manage banana stem waste. 3) Changing marketing strategy patterns from traditional to digital. The output targets to be achieved are publication in the SINTA 4 indexed journal, publication of service activities in electronic mass media, video documentation via YouTube channel, and posters containing PKM activities and achievements.